PERAN BANK SAMPAH DALAM PENGELOLAAN SAMPAH PLASTIK DI DEPOK - Caecilia Meyta Rahayuningtyas; Ahyahudin Sodri; Lina Tri Mugi Astuti (EnviroScienteae, 2023)
Plastic consumption continues to increase, which is influenced by population growth and increased use of plastic. Plastics that are flexible to be used as daily necessities, especially plastics that are widely used for packaging. This also increases the problem of plastic waste. Unmanaged and wasted plastic in landfills is an environmental problem. The purpose of this research is to analyze the role of waste banks in the utilization and management of plastic waste. The method used is a quantitative method with descriptive and mathematical analysis. The result of this research is that plastic can be utilized if it is clean and dry in segregated conditions. Community, government and recycler cooperation in collecting and utilizing plastic waste can increase the economic value of plastic waste. The important role of the community in sorting waste in households and waste banks at the RT/RW level in collecting inorganic waste. In conclusion, the role of the waste bank can improve people's habits in sorting inorganic waste and also increase the economic value of plastic waste.